Pengaruh Terapi Musik Klasik terhadap Respon Fisiologis pada Pasien yang Mengalami Kecemasan Praoperatif Ortopedi - Armansyah; Yecy Anggreny (STIKes Hang Tuah Pekanbaru, 2012)
Preparation of patients mental before to surgery is needed. If patients experience severe anxiety and panic operating plan will be delayed, it will allow a greater risk of infection. From various research show that music has a strong influence on health, especially in calming the mind, reduce physical tension and create a relaxed state, if the patient in a relaxed state is expected to affect physiological responses. The purpose of this study was to determine the effect of classical music therapy on physiological responses in patients who underwent orthopedic praoperatif anxiety. The study design is pre-experiment with a sample of 30 people using purposive sampling. Music therapy is given for ± 30 minutes. The analysis used were Paired Sample T Test and Wilcoxon. Obtained mean systolic blood pressure was 120.2 mmHg before therapy, after therapy 119.6 mmHg, p value = 0.227. Mean diastolic blood pressure before treatment was 74.1 mmHg, 73.2 mmHg after therapy is, p value = 0.133. Mean heart rate before treatment was 81.8 x / min, after therapy was 79 x / minute, p value = 0.005. Median respiratory frequency before treatment was 23 x / minute, after the therapy is 21 x / minute, p value = 0.001. This shows the classical music therapy has an influence on heart rate and respiratory frequency in patients who underwent orthopedic praoperatif anxiety. Researchers recommend the use of classical music therapy with a frequency of 2 to 3 times a day before patients undergo surgery in order to obtain an optimal relaxation effects.